Smartphone Use Changes Rating of Perceived Exertion and Biomechanics but Not Physiological Parameters During Gait on Treadmill: A Pilot Study - B. Viana, Ricardo (2020)
Introduction: The use of smartphones during walking changes biomechanical parameters, but less is known about rating of perceived exertion and physiological adjustments to walking activity. Objective: To evaluate rating of perceived exertion, biomechanical and physiological responses during gait on treadmill while typing on a smartphone. Methods: Thirty men performed five minutes of walking on a treadmill while typing on a smartphone (TYP) or during control conditions (walk without type on a smartphone, [CON]) in random order. Heart rate, systolic blood pressure, diastolic blood pressure, rating of perceived of exertion, stride frequency and stride length were evaluated. Results: Systolic blood pressure after CON and TYP was significantly higher than at rest, but there was no significant difference between conditions. There was no significant difference between diastolic blood pressure at rest, after CON, and after TYP. Heart rate after CON and TYP was 29.7% and 39.2% higher than at rest, respectively, but there was no significant difference between conditions. Rating of perceived of exertion after TYP was greater than after CON. Stride length during TYP was shorter than during CON. Conclusion: In conclusion, five minutes of walking while use smartphone changed rating of perceived exertion and biomechanics but not physiological parameters during gait.